Energy Definition and Dark Energy: A Thermodynamic Analysis - H. Moradpour; J. P. Morais Graça; I. P. Lobo; I. G. Salako (Advances in High Energy Physics)
Accepting the Komar mass definition of a source with energy-momentum tensor Tμν and using the thermodynamic pressure definition, we find a relaxed energy-momentum conservation law. Thereinafter, we study some cosmological consequences of the obtained energy-momentum conservation law. It has been found out that the dark sectors of cosmos are unifiable into one cosmic fluid in our setup. While this cosmic fluid impels the universe to enter an accelerated expansion phase, it may even show a baryonic behavior by itself during the cosmos evolution. Indeed, in this manner, while Tμν behaves baryonically, a part of it, namely, Tμν(e) which is satisfying the ordinary energy-momentum conservation law, is responsible for the current accelerated expansion.